Dakwah Strategies of Sharia Tourism: The Case of Gili Air, North Lombok - lalu ahmad zaenuri (Universitas Islam Negeri Mataram, 2018)
For the past few years, Lombok in particular and West Nusa Tenggara in general have not only been known as an island of thousand mosques, but also as a world tourist destination, particularly Shari’a compliance (halal) tourism. With such a new branding, respective stakeholders on the island should therefore make an effort to plan strategies for presenting the concept of halal tourism that serve and benefit both domestic and foreign tourists. Dakwah (Islamic propagation/preaching) can play an important role in strengthening local people’s faith while also balancing between religiosity and tourism. This study looks into how the halal tourism ‘brand’ can be manifested in Gili Air, one of the famous small islands of tourist destination located in the northern part of Lombok. The study reveals that the dakwah strategies for shari’a tourism in Gili Air are carried out through twofold strategies, namely da‘wah bi al-lisān and da‘wah bi al-ḥāl. The first refers to a model where the activities of propagation revolve around preaching of Islamic tenets. The latter emphasizes actualization of Islamic doctrines into daily life.